Eksistensi Pertumbuhan Laba pada Perusahaan di Jakarta Islamic Index (JII) (Tahun 2016-2018) - Sofhian Sofhian (Al-Ulum, 2020)
This study aims to determine the partial profit growth of company stock prices (companies registered in the Jakarta Islamic Index - JII). The article is the result of stock analysis and annual financial statements of companies that enter the 2016-2018 Jakarta Islamic Index, by using a quantitative research. The sample used was obtained from 90 Jakarta Islamic Index companies using the simple regression analysis method. From the results of the hypothesis test, the variable earnings growth showed no significant effect on stock prices at companies listed on the Jakarta Islamic Index (JII). From the results of partial testing between earnings growth variables and stock price variables, the T count is smaller than the T table with a value of 0.436 <1.987 and a sig value of 0.664 is greater than 0.05. Therefore, it can be said that the profit growth variable does not have a significant effect on stock prices. According to the researchers, this occurs because there are other influences, one of which is the fluctuation of the rupiah exchange rate against foreign currencies.